Maintenance organization at Universiti Tun Hussein Onn Malaysia (UTHM) - Yasin, Mohd Norazam; Abdullah, Abd Halid; Mustakim, Fajaruddin; Abd. Hamid, Abd. Rahim; Singh, Bachan (Trans Tech Publications, 2015)
Proper maintenance of buildings is to extend the life span of buildings [1]. In order to maintain the buildings, apart from maintenance work, is the organization aspect, one of the important elements in building maintenance [3]. The organization will have to be carefully structured and designed so that the staff can function efficiently [8,9,10,11,13]. The staff will have to be given training from time to time so that they are acquainted with the current technology and to tackle the challenges [6,12]. The objectives of this study are to examine the current maintenance organizational structure, to identify the main problems faced by the maintenance staff, to evaluate the level of job satisfaction and to identify the types of training to be provided to the maintenance staff. The study is carried through questionnaires and interviews. A total of fifty (50) questionnaires are distributed to the respondents consisting of engineers, technical assistants and technicians. The data is analyzed using average index. From the study, it was found that the type of organization structure of the maintenance department in UTHM is of line and staff.